Sensory modulation of movement, posture and locomotion - Saradjian, A.H. (Neurophysiologie clinique, 2015)
During voluntary movement, there exists a well known functional sensory attenuation of afferent inputs, which allows us to discriminate between information related to our own movements and those arising from the external environment. This attenuation or ‘gating’ prevents some signals from interfering with movement elaboration and production. However, there are situations in which certain task-relevant sensory inputs may not be gated. This review begins by identifying the prevalent findings in the literature with specific regard to the somatosensory modality, and reviews the many cases of classical sensory gating phenomenon accompanying voluntary movement and their neural basis. This review also focuses on the newer axes of research that demonstrate that task-specific sensory information may be disinhibited or even facilitated during engagement in voluntary actions. Finally, a particular emphasis will be placed on postural and/or locomotor tasks involving strong somatosensory demands, especially for the setting of the anticipatory postural adjustments observed prior the initiation of locomotion. Durant le mouvement volontaire, il est communément admis qu’une atténuation sensorielle fonctionnelle des entrées afférentes est exercée, dans le but de pouvoir discerner les afférences émanant de son propre mouvement de celles émanant de l’environnement extérieur, permettant ainsi de ne pas parasiter l’élaboration et la production motrice. Il existe néanmoins des contextes où une afférence sensorielle en question n’a pas vocation à être atténuée selon la pertinence de tâche à exécuter. Cette revue liste, plus précisément pour la modalité somesthésique, les cas d’atténuations sensorielles classiques accompagnant le mouvement volontaire retrouvés dans la littérature ainsi que leurs bases neurales ; mais également des tâches requérant fortement l’implication d’une afférence spécifique et pour lesquelles on observera une levée d’inhibition, voire une facilitation sensorielle. Enfin, un accent particulier sera mis sur des tâches posturales et/ou locomotrices requérant fortement des entrées somatosensorielles pour la calibration de processus préparatoires au mouvement, notamment la mise en place d’ajustements posturaux anticipés précédant l’initiation de la locomotion.